AN ATTEMPT TO PROVE CHRISTIAN GOLDBACH’S CONJECTURE - Robson Barros, Antonio (Journal of Interdisciplinary Debates, 2025)
The purpose of this work is to present an attempt to demonstrate Christian Goldbach’s conjecture (1690, 1764) commented on on pages 8 to 12. Therefore, the aforementioned theme contributes positively to the teaching-learning process and has an essential focus on research.